Governing Environmentally-Related Migration in Bangladesh: Responsibilities, Security and the Causality Problem. (June 2013) - Mayer, Benoît; Boas, Ingrid; Ewing, J. Jackson; Baillat, Alice; Das, Uttam Kumar
Environmentally-related migration is often cited as one of the human consequences of environmental stress, especially in the context of climate change. Nonetheless, there is a lack of effective and appropriate governance strategies that address the issue due to the complex and multicausal character of environmentally-related migration and the tendency to discuss the issue through security-based discourses that favor alarmist narratives. This paper suggests alternative approaches in responding to environmentally-related migration that seek to avoid these pitfalls. Through the case of Bangladesh, this paper illustrates the need to form cross-sectoral governance policies that avoid oversimplifying environmentally-related migration. Specifically, the paper highlights the limits and dangers of the security-based framework to environmentally-related migration and calls for policy coordination as a potential pathway forward.